Comprehensive genome analysis uncovers the diversity of jumbo phages in the pig gut microbiome - Wei, Chao; Chen, Zhe (Frontiers in Veterinary Science, 2026)
Gut microbiome research has historically focused on bacterial communities. In contrast, the roles of viruses, especially jumbo phages, remain poorly understood. Jumbo phages are of major interest because their large genomes encode unique functions that can influence host metabolism and ecosystem dynamics. This study bridges this gap by identifying 1,545 jumbo phage genomes from 450 pig gut metagenomes. Using CRISPR spacer analysis, we predicted archaeal or bacterial hosts and reconstructed competitive phage networks within this ecosystem. Phylogenetic divergence combined with orthologous protein comparisons supported establishing 14 novel jumbo phage families. Functionally, 10 of these novel families encode auxiliary metabolic genes (AMGs) that enhance host metabolism alongside anti-defense systems including DNA methyltransferases, HNH endonucleases, and glycosyltransferases. Ecological interactions were further elucidated through co-abundance networks (n = 857 pairs) and CRISPR spacer matching (n = 425 pairs), revealing relationships between novel jumbo phages and other jumbo phages. Collectively, this work expands genomic resources for pig gut viromes and delivers new insights into jumbo phages’ functional capabilities, host associations, and global prevalence.